Experienced safety across ward types in forensic psychiatry - Verstegen, Nienke (The journal of forensic psychiatry & psychology, 2022)
In high security forensic institutions, patients are sometimes placed on small-scale wards to be treated individually if their psychiatric condition and behaviour do not allow for them to live and interact more freely with other patients. On these so-called individual wards, there is little contact between patients and more security measures are in place, such as higher numbers of staff members per patient than on group wards. The present study investigated the experienced safety of staff members (n = 41) and patients (n = 21) of such individual wards, compared to staff members (n = 55) and patients (n = 55) of group wards with the Essen-CES. The mean item score on the scale experienced safety of the Essen-CES for the entire sample was 2.1 (SD = .9) with a range from 0 to 4 and higher scores reflecting a higher experienced safety. Staff on individual wards had a significantly lower experienced safety than patients on both ward types and staff on group wards. It is advised, therefore, to implement additional measures to support professionals who work on these individual wards.